Penentuan Interval Penggantian Komponen Pada Motor Listrik Untuk Meminimalkan Resiko Downtime di PT. Wilmar Nabati Indonesia - Guritno Catur Pamungkas (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
The Failure of production machines in PT. Wilmar Nabati Indonesia can make serious problem, because it can stop process production and increase breakdown time while waiting machines repaired by technician. Company doesn’t want this problem, because it can effect on planning and controlling production and decrease the achievement of production target. So target of production can’t be full filled.Based on the analitic and intrepetation on this paper, we can take a conclusion from this research, the conclusion are the higest failure frequency in component of electrical motoric machine is in a bearings component. Optimalized interval time is 17 days and downtime value is 0,01946, based on calculation of age replacement model with minimation of downtime crirteria. In that interval, we can know that failure probability of component is 0,02888 and reliability of component is 0,7054 ≈ 0,7: based on the calculation also we can know that failure rate is 0,040016